2006
DOI: 10.1590/s0365-05962006000300011
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteróide tópico oclusivo no tratamento de manifestações gengivais de doenças vesicobolhosas auto-imunes

Abstract: Management of gingival lesions of vesicobullous autoimmune diseases is one the main challenges to oral medicine, primarily because of their chronic nature. Systemic therapy is required in most severe lesions, however, whenever feasible, topic corticosteroid therapy is preferred. This article describes a technique to provide topical occlusive corticotherapy that has shown to be effective in controlling these lesions, especially in patients exclusively with gingival lesions. Keywords: Adrenal cortex hormones; Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…As for BMMP and its clinical signs, some studies have shown that desquamative gingivitis can be present in up to 95% of cases [5,11,12]. Erosive flat lichen and, less frequently, pemphigus vulgaris may also cause desquamative gingivitis [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for BMMP and its clinical signs, some studies have shown that desquamative gingivitis can be present in up to 95% of cases [5,11,12]. Erosive flat lichen and, less frequently, pemphigus vulgaris may also cause desquamative gingivitis [5].…”
Section: Discussionmentioning
confidence: 99%
“…The changes caused by BMMP in the oral epithelium affect periodontal health, facilitating the accumulation of dental biofilm and changing periodontal parameters. Bleeding, probing depth, and the clinical insertion level may make diagnosing the condition challenging due to the overlapping clinical signs of different autoimmune diseases and periodontal changes [3,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation